Genomic Epidemiology and Phenotyping Reveal on-Farm Persistence and Cold Adaptation of Raw Milk Outbreak-Associated Yersinia pseudotuberculosis - Castro, Hanna; Jaakkonen, Anniina; Hakakorpi, Anna; Hakkinen, Marjaana; Isidro, Joana; Korkeala, Hannu; Lindström, Miia; Hallanvuo, Saija (Frontiers in Microbiology, 2019)
Packaged raw milk contaminated with Yersinia pseudotuberculosis mediated a large yersiniosis outbreak in southern Finland in 2014. The outbreak was traced back to a single dairy farm in southern Finland. Here we explore risk factors leading to the outbreak through epidemiologic investigation of the outbreak farm and through genomic and phenotypic characterization of the farm’s outbreak and non-outbreak associated Y. pseudotuberculosis strains. We show that the outbreak strain persisted on the farm throughout the seven-month study, whereas the non-outbreak strains occurred sporadically. Phylogenomic analysis illustrated that the outbreak strain was related to previously published genomes of wild animal isolates from Finland, implying that wild animals were a potential source of the outbreak strain to the farm. We observed allelic differences between the farm’s outbreak and non-outbreak strains in several genes associated with virulence, stress response and biofilm formation, and found that the outbreak strain formed biofilm in vitro and maintained better growth fitness during cold stress than the non-outbreak strains. Finally, we demonstrate the rapid growth of the outbreak strain in packaged raw milk during refrigerated storage. This study provides insight of the risk factors leading to the Y. pseudotuberculosis outbreak, highlights the importance of pest control to avoid the spread of pathogens from wild to domestic animals, and demonstrates that the cold chain is insufficient as the sole risk management strategy to control Y. pseudotuberculosis risk associated with raw drinking milk.